Some Fixed point theorems in Complex Valued Metric Space using Weak Compatible Mappings - Lekshmi .S and K.S.Dersanambika (International Journal of Emerging Trends in Science and Technology, 2017)
The aim of the present paper is to establish fixed point theorems for self mappings under weakly compatibility in Complex valued metric space.